2016
DOI: 10.1177/1747493016654489
|View full text |Cite
|
Sign up to set email alerts
|

Remote limb ischemic conditioning treatment for intracranial atherosclerotic stenosis patients

Abstract: We predict that RLIC treatment for 12 months will safely reduce the ischemic stroke recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(62 reference statements)
1
8
1
Order By: Relevance
“…(1) Acute ischemic stroke [ 146 , 147 ], RIC treatment after acute stroke was likely to lower the risk of tissue infarction after 1 month, and improve the neurological outcome as depicted by a reduction in day 90 median National Institutes of Health Stroke Scale (NIHSS) score; (2) chronic cerebral ischemia [ 142 , 143 , 148 , 149 ], daily use of bilateral upper limb RIC was safe, tolerable, and able to reduce the recurrence of stroke/transient ischemic attack (TIA), improve cerebral perfusion as well as ameliorate the processes of inflammation, coagulation and fibrinolysis; (3) subarachnoid hemorrhage [ 150 155 ], the feasibility and tolerability of RIC were denoted in several proof-of-concept trials; (4) carotid endarterectomy and stenting (CEA and CAS) [ 156 , 157 ], a trend toward fewer saccadic latency deteriorations and a significant reduction in the incidence of new DWI lesions were observed among patients who received RIC; (5) cerebral small-vessel disease [ 158 160 ], RIC appeared to be effective in retarding cognition decline and decreasing white matter lesions; and (6) traumatic brain injury [ 161 ], it was found that RIC markedly reduced the serum levels of neuron-specific enolase (NSE) and S-100β.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Acute ischemic stroke [ 146 , 147 ], RIC treatment after acute stroke was likely to lower the risk of tissue infarction after 1 month, and improve the neurological outcome as depicted by a reduction in day 90 median National Institutes of Health Stroke Scale (NIHSS) score; (2) chronic cerebral ischemia [ 142 , 143 , 148 , 149 ], daily use of bilateral upper limb RIC was safe, tolerable, and able to reduce the recurrence of stroke/transient ischemic attack (TIA), improve cerebral perfusion as well as ameliorate the processes of inflammation, coagulation and fibrinolysis; (3) subarachnoid hemorrhage [ 150 155 ], the feasibility and tolerability of RIC were denoted in several proof-of-concept trials; (4) carotid endarterectomy and stenting (CEA and CAS) [ 156 , 157 ], a trend toward fewer saccadic latency deteriorations and a significant reduction in the incidence of new DWI lesions were observed among patients who received RIC; (5) cerebral small-vessel disease [ 158 160 ], RIC appeared to be effective in retarding cognition decline and decreasing white matter lesions; and (6) traumatic brain injury [ 161 ], it was found that RIC markedly reduced the serum levels of neuron-specific enolase (NSE) and S-100β.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of remote conditioning in general and the concept of rPostC in particular are interesting concepts for adjuvant treatment paradigms of different diseases. Indeed, first clinical trials have been performed, suggesting possible beneficial effects after remote conditioning ( Zuo et al, 2015 ; Bei et al, 2016 ; Hou et al, 2016 ; England et al, 2017 ; Wang et al, 2017 ; Zhao et al, 2017 ; Zhou et al, 2017 ). Yet, the study concepts are heterogeneous, including small study populations with special medical conditions only.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the study concepts are heterogeneous, including small study populations with special medical conditions only. Leaving aside clinical trials on various settings of renal malfunction ( Bei et al, 2016 ; Zuo et al, 2015 ; Zhou et al, 2017 ) as well as trials on chronic vessel diseases of the brain ( Hou et al, 2016 ; Wang et al, 2017 ; Zhao et al, 2017 ), the RECAST study remains the only clinical trial where rPostC has been applied as a therapeutic means to counter a territorial ischemic stroke during the acute phase of the disease ( England et al, 2017 ). Of note, rPostC in the RECAST trial like in the RESCUE BRAIN trial, which is currently recruiting ( Pico et al, 2016 ), treatment starts within 24 h post-stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its protective effects in the heart and brain, RLIC has been shown to exert protective effects in several other organs such as the lungs, kidneys, and liver (24). While RLIC applications are currently limited to cases of acute ischemia, recent studies have revealed the protective effects of RLIC against the effects of chronic decreases in blood supply in the brain (8, 9, 2527) and heart (28), such as those associated with CCCI and stable coronary artery disease.…”
Section: Overview Of Remote Limb Ischemic Conditioning (Rlic)mentioning
confidence: 99%